1995
DOI: 10.1002/ijc.2910640114
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic progression of human colorectal cancer is associated with overexpression of the stromelysin‐3 and BM‐40/SPARC genes

Abstract: The interaction of neoplastic cells with the extracellular matrix is a critical event for the initiation of cancer invasion and metastasis. This study was designed to evaluate the potential implication of stromelysin-3 (ST3), a newly identified member of the matrix-degrading metalloproteinase family, and of BM-40/SPARC, a glycoprotein associated with the extracellular matrix, during the progression of human colorectal cancers. We analyzed the relative abundance of ST3 and BM-40/SPARC transcripts by Northern bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
131
0
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 21 publications
11
131
0
3
Order By: Relevance
“…17 SPARC overexpression has previously been associated with human tumors. 20 Porte et al 21 identified an association of SPARC with colorectal carcinoma, where neoplastic progression was associated with overexpression of the stromelysin-3 and SPARC genes. Massi et al 22 demonstrated in 188 patients with thin (Ͻ0.75 mm) melanoma that SPARC positivity on IHC staining correlated with significantly poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…17 SPARC overexpression has previously been associated with human tumors. 20 Porte et al 21 identified an association of SPARC with colorectal carcinoma, where neoplastic progression was associated with overexpression of the stromelysin-3 and SPARC genes. Massi et al 22 demonstrated in 188 patients with thin (Ͻ0.75 mm) melanoma that SPARC positivity on IHC staining correlated with significantly poorer survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings complement the results of previous studies that reported alterations in SPARC expression in various human cancers. The overexpression of SPARC has been detected in melanoma (Ledda et al, 1997a), colorectal cancer (Porte et al, 1995), breast cancer (Bellahcene and Castronovo, 1995), hepatocellular carcinoma (Le Bail et al, 1999), invasive meningiomas , and prostate cancer (Thomas et al, 2000). Moreover, it has been reported that SPARC promotes cell migration and invasion in prostate cancer (Jacob et al, 1999) and glioblastoma (Golembieski et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In the adult, it becomes more restricted, but can be activated in pathologic situations like wound healing (Reed et al, 1993). However, recent evidence suggests that alterations in SPARC expression are common in various human malignancies, including melanoma (Ledda et al, 1997b), glioma (Schultz et al, 2002), invasive meningioma , hepatocellular carcinoma (Le Bail et al, 1999), colon (Porte et al, 1995), breast (Gilles et al, 1998), and prostate (Thomas et al, 2000) cancers. To date, however, there are no detailed studies on SPARC expression in BE and Barrett's-associated adenocarcinoma (EA) of the oesophagus.…”
mentioning
confidence: 99%
“…In a study evaluating stromelysins 1 and 2 and matrilysin (PUMP-1) expression in colorectal cancer, the mRNA of the latter enzyme was expressed in 75% of colon carcinomas, whereas the mRNA of the former was not detected (McDonnell et al, 1991). In a recent study, stromelysin 3 mRNA was overexpressed in primary colorectal adenocarcinomas and liver metastases and expression was shown in stromal fibroblasts adjacent to the neoplastic lesions (Porte et al, 1995).…”
mentioning
confidence: 99%
“…In a study evaluating stromelysins 1 and 2 and matrilysin (PUMP-1) expression in colorectal cancer, the mRNA of the latter enzyme was expressed in 75% of colon carcinomas, whereas the mRNA of the former was not detected (McDonnell et al, 1991). In a recent study, stromelysin 3 mRNA was overexpressed in primary colorectal adenocarcinomas and liver metastases and expression was shown in stromal fibroblasts adjacent to the neoplastic lesions (Porte et al, 1995).A study examining collective expression of gelatinases and matrilysin suggested that the latter may participate early in tumour progression, whereas the former enzymes, in conjunction with matrilysin and other members of the MMP family, may mediate events occurring later in the progressive cascade (Newell et al, 1994).The synthetic metalloproteinase inhibitor, batimastat, has broad spectrum and potent activity against many members of the MMP family (Brown, 1993) and has been shown to inhibit the metastatic spread of the B16 murine melanoma (Chirivi et al, 1994) and the lung and liver colonisation of the human colorectal tumours, AP5LV and C1 70HM2 respectively (Watson et al, 1995). In addition, the agent has been shown to inhibit tumour growth in an ovarian ascites model (Davies et al, 1993).…”
mentioning
confidence: 99%